Perception of Factors Affecting Studies and Well–Being: A Dental Student Perspective - Hotchandani, Sarang Suresh; Harjani, Priya Rani; Shaikh, Muhammad Ilyas; Khatoon, Safia (European Dental Research and Biomaterials Journal, 2020)
Objective This study aimed to assess the perception of factors affecting studies and well-being among students of the Bibi Aseefa Dental College, Larkana, Sindh, Pakistan.Materials and Methods Students of the Bibi Aseefa Dental College of various professional years were asked to respond to an online-based survey (Google Forms), which was then evaluated by SPSS 16.0 (SPSS Inc.; Chicago Illinois, United States) using the analysis-of-variance test. The study sample consisted of stratified random sampling. Inclusion criteria included students from year 1 to year 4 of their undergraduate studies during the study period of June 2019 to August 2019. Descriptive statistics including frequency and distribution regarding gender, year of study, age, external factors (stress, sleep, health, hobbies, financial, friends, paid work, voluntary work), reasons for choosing dentistry, and how these factors affecting the study were created.Results The results showed that 97 students chose Bachelor of Dental Study (BDS) as a career because they were not selected in Bachelor of Medicine and Bachelor of Surgery (MBBS). Overall, 52.41% students agreed that external factors are affecting their studies, 46.8% stated that they were stressed due to studies in past 12 months, 48.4% students agreed that their disturbed sleep due to academic assignments is affecting their studies, 29.9% stated that their health disturbance affected their studies in the past 12 months, and 48.4% responded that their own hobbies and sports work were affecting their academic grades.Conclusion This study revealed that extracurricular factors were a cause of stress among dental students. The main cause of stress among the student was confusion about the syllabus of their academic year, resulting in a lack of sleep during the examination year, and favoritism among teachers for the students.
Keywords: stress factors; academic; dental students; survey